The spring back effect of oil palm empty fruit bunch fibre on physical and mechanical properties of cement board - Nik Soh, Nik Mohd Zaini (2022)
The inclusion of oil palm empty fruit bunch fibre (EFB) in cement board has promoted the internal stress development called spring back (SpB). Theoretically SpB has increased the thickness and decreases the density of the sample, and eventually decline the physical and mechanical properties of empty fruit bunch cement board (EFBCB). The main factors that have identified to contribute SpB are the length of fibres used, the ratio of cement to fibres and incompatibility between fibres and cement. Hence, this study was conducted to propose an effective approach to mitigate the effect of SpB on EFBCB samples to expedite corrective action especially along curing period. Three groups of samples namely EFB length, cement-EFB ratio and percentage NaOH concentration for EFB treatment were prepared, where each of design mixed consists of 5 repeated samples. Modulus of elasticity (MOE), modulus of rupture (MOR), internal bonding (IB) and thickness swelling (TS) are the properties that were investigated for EFBCB sample. The results revealed that combination EFB length of 16% of 25.72 mm, 64% of 14.37 mm and 20% of 4.32 mm with cement to EFB ratio of 3:1 and 3% NaOH concentration for EFB treatment has yielded optimum physical and mechanical properties. This combination has significantly diminished the SpB effect and produced MOE, MOR, IB, and TS values of 6098 N/mm2, 11.92 N/mm2, 0.53 N/mm2, and 1.22%, respectively. On top of that, the linear regression prediction model based on cement to EFB ratio and percentage of NaOH concentration for EFB treatment discovered that the maximum percentage of thickness increment due to SpB is found to be limited to 3.2% or 0.4 mm in sustaining the standard requirement. Therefore, the limit of percentage thickness increment (3.2%) has been incorporated in new laboratory technique to mitigate the SpB effect of EFB on EFBCB sample. Thus, the corrective measures can be done as early as day 2 to day 15 during the curing period for the samples with a thickness exceeding 12.4 mm (3.2% of design thickness). It can be concluded that, the reduction in thickness increment due to SpB significantly improve the performance of EFBCB samples as well as failed of EFBCB samples can be identified as earlier as during curing period purposely for design mix correction.